Sex differences in PTSD speech biomarkers assessed by virtual agent-induced conversations - Menne, Felix; Schwed, Louisa; Dörr, Felix; Linz, Nicklas; Tröger, Johannes; König, Alexandra (Frontiers in Psychology, 2025)
IntroductionWomen face a substantially elevated risk of developing PTSD compared to men. With the emergence of automated digital biomarkers for assessing complex psychiatric disorders, it becomes imperative to take into account possible sex differences.ObjectivesOur objective was to explore sex-related speech differences in individuals with PTSD.MethodsWe utilized data from the DAIC-WOZ dataset, consisting of dialogs between participants with PTSD (n = 31) and a virtual avatar. Throughout these dialogs, the avatar utilized diverse prompts to maintain a conversation. Features were extracted from the transcripts, and acoustic features were obtained from the recorded audio files. Group comparisons, correlations, and linear models were calculated to assess sex-related differences in these features between male and female individuals with PTSD.ResultsGroup comparisons yielded significant differences between male and female patients in acoustic features such as the F2 frequency Standard Deviation (higher in males) and Harmonics to Noise Ratio (lower in males). Correlations revealed that Loudness Standard Deviation was significantly associated with PCL-C scores in males, but not in females. Additionally, we found interaction effects for linguistic and temporal features such as verb phrase usage, adposition rate, mean utterance duration, and speech ratio, with males showing positive associations and females showing inverse associations.ConclusionSex-related variations in the expression of PTSD severity through speech suggest contrasting effects in acoustic and linguistic features. These results underscore the importance of considering sex-specific expressions of behavioral symptoms in developing digital speech biomarkers for diagnostic and monitoring purposes in PTSD.